Generation of Multiple Isoforms of Eukaryotic Translation Initiation Factor 4GI by Use of Alternate Translation Initiation Codons - Byrd, Marshall P. (American Society for Microbiology, 2002)
Eukaryotic translation initiation factor 4GI (eIF4GI) is an essential protein that is the target for translational regulation in many cellular processes and viral systems. It has been shown to function in both cap-dependent and cap-independent translation initiation by recruiting the 40S ribosomal subunit to the mRNA cap structure or internal ribosome entry site (IRES) element, respectively. Interestingly eIF4GI mRNA itself has been reported to contain an IRES element in its 5′ end that facilitates eIF4GI protein synthesis via a cap-independent mechanism. In HeLa cells, eIF4GI exists as several isoforms that differ in their migration in sodium dodecyl sulfate (SDS) gels; however, the nature of these isoforms was unclear. Here, we report a new cDNA clone for eIF4GI that extends the 5′ sequence 340 nucleotides beyond the previously published sequence. The new extended sequence of eIF4GI is located on chromosome 3, within two additional exons immediately upstream of the previously published eIF4GI sequence. When mRNA transcribed from this cDNA clone was translated in vitro, five eIF4GI polypeptides were generated that comigrated in SDS-polyacrylamide gels with the five isoforms of native eIF4GI. Furthermore, translation of eIF4GI-enhanced green fluorescent protein fusion constructs in vitro or in vivo generated five isoforms of fusion polypeptides, suggesting that multiple isoforms of eIF4GI are generated by alternative translation initiation in vitro and in vivo. Mutation of two of the five in-frame AUG residues in the eIF4GI cDNA sequence resulted in loss of corresponding polypeptides after translation in vitro, confirming alternate use of AUGs as the source of the multiple polypeptides. The 5′ untranslated region of eIF4GI mRNA also contains an out-of-frame open reading frame (ORF) that may down-regulate expression of eIF4GI. Further, data are presented to suggest that a proposed IRES embedded in the eIF4GI ORF is able to catalyze synthesis of multiple eIF4GI isoforms as well. Our data suggest that expression of the eIF4GI isoforms is partly controlled by a complex translation strategy involving both cap-dependent and cap-independent mechanisms.